Exogenous platelet-derived growth factor improves neurovascular unit recovery after spinal cord injury - Lu-Xia Ye; Ning-Chen An; Peng Huang; Duo-Hui Li; Zhi-Long Zheng; Hao Ji; Hao Li; Da-Qing Chen; Yan-Qing Wu; Jian Xiao; Ke Xu; Xiao-Kun Li; et al. (Neural Regeneration Research, 2021)
The blood-spinal cord barrier plays a vital role in recovery after spinal cord injury. The neurovascular unit concept emphasizes the relationship between nerves and vessels in the brain, while the effect of the blood-spinal cord barrier on the neurovascular unit is rarely reported in spinal cord injury studies. Mouse models of spinal cord injury were established by heavy object impact and then immediately injected with platelet-derived growth factor (80 μg/kg) at the injury site. Our results showed that after platelet-derived growth factor administration, spinal cord injury, neuronal apoptosis, and blood-spinal cord barrier permeability were reduced, excessive astrocyte proliferation and the autophagy-related apoptosis signaling pathway were inhibited, collagen synthesis was increased, and mouse locomotor function was improved. In vitro, human umbilical vein endothelial cells were established by exposure to 200 μM H2O2. At 2 hours prior to injury, in vitro cell models were treated with 5 ng/mL platelet-derived growth factor. Our results showed that expression of blood-spinal cord barrier-related proteins, including Occludin, Claudin 5, and β-catenin, was significantly decreased and autophagy was significantly reduced. Additionally, the protective effects of platelet-derived growth factor could be reversed by intraperitoneal injection of 80 mg/kg chloroquine, an autophagy inhibitor, for 3 successive days prior to spinal cord injury. Our findings suggest that platelet-derived growth factor can promote endothelial cell repair by regulating autophagy, improve the function of the blood-spinal cord barrier, and promote the recovery of locomotor function post-spinal cord injury. Approval for animal experiments was obtained from the Animal Ethics Committee, Wenzhou Medical University, China (approval No. wydw2018-0043) in July 2018.